Work Duration and Working Posture on Musculoskeletal Disorders (MSDs) in Inter-City Inter-Provincial Bus Drivers at Mengwi Terminal - Wira Laksana, Dewa Gede Bagus; Budiapsari, Putu Indah; Rusni, Ni Wayan (Muhammadiyah Medical Journal, 2025)
Background: Every job has risks caused by the work environment, tools, and processes. One of the diseases resulting from work risks that most often appears among workers is Musculoskeletal Disorders (MSDs). One of the factors that can influence the occurrence of musculoskeletal complaints is work duration and work posture. MSDs complaints can be measured using the Nordic Body Map (NBM). This work posture is measured by the Rapid Upper Limb Assessment (RULA) questionnaire. Purposes: This study aims to determine the correlation between duration and work posture toward musculoskeletal disorders in inter-city inter-provincial bus drivers at Mengwi Terminal. Methods: This research uses an analytical design with a cross-sectional study or cross-sectional approach. Sampling was carried out by consecutive sampling. Based on the sample size formula, a minimum 30 plus 10% sample was obtained to make 33 respondents. In this research, the author will use 40 respondents. The data received will be analyzed univariately and bivariately using the SPSS version 25 application with the Spearman correlation test. The significance level is p < 0.05 with a CI of 95%. Results: The research results show the following: there is a significant correlation between work duration and attitude with MSDs (r=0.674) for work duration and (r=0.574) for working posture. Conclusion: It can be concluded that the correlation between duration and work attitudes and MSDs is strong. Employees are recommended to minimize work duration and have a work attitude with an ergonomic approach.